مقدمات المعاجم – دراسة نماذج مختارة - هندة غنام (My University, 2023)
summary : The Arab heritage is full of many rich lexical works with different titles, different contents, and the lexicon is the indispensable basic source and is considered the wanderer of anyone on whom a certain word is closed, so it will be the provision , the ammunition and the wealth with which each nation preserves its vocabulary heritage, and we studied three dictionaries, namely: the Al-Ain lexicon of Khalil Bin Ahmed Al-Farahidi, which is the first complete Arabic dictionary in history of the Arabic language, and the lexicon of Lisan Al-Arab La Bin Manzoor, because it is one of the largest Arabic dictionaries which stood out for perfection, care and explanation, and the dictionary Al- Muheet of Al-Fayrouzabadi, who distinguished himself by mentioning morphological balance on The Method of Morphological Scholars, and this feature is unique to him among all other dictionaries. ---------------- ملخص : يزخر التراث العربي بالعديد من الأعمال المعجمية الثرية المتباينة العناوين ، المختلفة المضامين ،والمعجم هو المصدر الأساس الذي لا غنى عنه ويعد ضالة كل إنسان استغلقت عليه لفظة معينة، فيكون بذلك الزاد و الذخيرة و الثروة التي تحفظ بها كل امة تراثها المفرداتي ، وقد قمنا بدراسة ثلاثة معاجم وهي : معجم العين للخليل بن احمد الفراهيدي ،وهو أول معجم عربي شامل في تاريخ اللغة العربية ، ومعجم لسان العرب لا بن منظور فهو من أضخم المعاجم العربية الذي تميز بالإتقان و العناية و الشرح ، والقاموس المحيط للفيروز آبادي و الذي تميز بذكر الميزان الصرفي على طريقة علماء الصرف ، وهذه الميزة انفرد بها عن سائر المعاجم الأخرى ---------------- résumé : Le patrimoine arabe regorge de nombreux ouvrages lexicaux riches avec des titres différents, des contenus différents, et le lexique est la source de base indispensable et est considéré comme le vagabond de toute personne sur laquelle un certain mot est fermé, il en sera donc la provision, les munitions et la richesse avec lequel chaque nation préserve son patrimoine de vocabulaire, et nous avons étudié trois dictionnaires, à savoir : le lexique Al-Ain de Khalil Bin Ahmed Al-Farahidi, qui est le premier dictionnaire arabe complet de l'histoire de la langue arabe, et le lexique de Lisan Al-Arab La Bin Manzoor, car c'est l'un des plus grands dictionnaires arabes qui s'est distingué par la perfection, le soin et l'explication, et le dictionnaire Al-Muheet d'Al-Fayrouzabadi, qui s'est distingué en mentionnant l'équilibre morphologique sur La méthode des savants morphologiques , et cette fonctionnalité lui est unique parmi tous les autres dictionnaires